Combined Effects of Banana Peels and Pith as Dual Natural Plant-Based Coagulants for Turbidity Removal - Rayer, Esther Jebarani; Muhamad, Mimi Suliza; Mohd Apandi, Najeeha; Mohamed Sunar, Norshuhaila; Ali, Roslinda (semarak ilmu, 2024)
Plant-based coagulants are foreseen for their coagulation ability in par with chemical coagulants owing to their biodegradability, availability, and effectiveness, while chemical coagulants are known to pose a threat to the environment due to generation of toxic sludge. This study investigates the performance of combined banana peels and banana pith as dual natural plant-based coagulants for turbidity removal. Banana peel powder solution (BPPS), banana pith juice (BPJ), and the combination of BPPS and BPJ were prepared via several steps, including drying, grinding, sieving, mixing, and crushing. The three types of coagulant produced were tested in a series of jar test experiments under the effects of different dosages, pH, and mixing speeds. The scanning electron microscopy images of banana pith show the formation of multicellular fibers, while irregular shapes and micro-rough crate-like pores are formed in banana peels, which contribute to the adherence of contaminants. Jar test results revealed the highest turbidity removal of 97.3, 98.0, and 99.1% was attained by using 60, 80, and 20:20 mg/L of banana peel powder solution, banana pith juice, and a combination of banana peel powder solution and banana pith juice coagulant dosage, respectively, with an optimum pH of 2, at a rapid mixing rate of 180 rpm (5 minutes) and a slow mixing of 60 rpm (20 minutes). Significantly, this removal was attributed to the presence of proteins and polysaccharides in both banana peels and pith. The findings suggested that banana peels and pith are applicable as natural plant-based coagulants for turbidity removal in the water treatment process and a potential substitute for conventional coagulants. In addition, the combined banana peels and banana pith coagulant prove to be more efficient than the existing banana peels and banana pith coagulant.